Communication skills teaching for student dietitians using experiential learning and simulated patients. Issue 5 (28th May 2020) - Knight, A.; Baldwin, C.; Reidlinger, D. P.; Whelan, K.
Abstract: Background: Dietitians require communication competencies for effective dietetic practice. There is little evidence on how student dietitians experience and value communication skills teaching. The present study aimed to measure attitudes of student dietitians with respect to communication skills teaching and how experiential learning using simulated patients impacts confidence in their communication skills. Methods: Communication skills teaching adopting an experiential skills‐based approach including practice with simulated patients, feedback and reflection were developed. A 67‐item questionnaire with three sections: (i) views regarding the importance of communication skills to dietetic practice; (ii) attitudes to learning communication skills using a modified Communication Skills Attitude Scale; and (iii) confidence in their own communication skills, was completed by students before and after the course, with responses recorded on a five‐point Likert scale and analysed pairwise using McNemar's test. Results: Over three academic years, 112 students (91.8% response rate) completed the evaluation. After training, students rated communication skills as important for patient satisfaction (100%) and relationships with patients (99.1%). Student dietitians had positive attitudes to learning communication skills with positive attitudes scale score before teaching of mean (SD) 53.6 (5.3) and after of 54.0 (5.8) ( P = 0.162). Following experiential teaching, the proportion of students feeling 'very or extremely confident' in understanding a patient's perspective increased from 27.7% to 41.1% ( P = 0.008) and for reaching agreement with a patient from 4.5% to 17.9% ( P = 0.001). Conclusions: Student dietitians consider communication skills important for dietetic practice. They receive teaching positively and an experiential skills‐based approach can improve self‐rated confidence. Abstract : Communication skills teaching adopting an experiential skills‐based approach including practice with simulated patients, feedback and reflection were developed for student dietitians. Student dietitians consider communication skills important for dietetic practice. They receive teaching positively and an experiential skills‐based approach can improve self‐rated confidence.